Impacts of Geological Formations on Quality of Groundwater - Motlagh , Kh. Shafiei (Technium EcoGeoMarine, 2022)
Sedimentary environment and impacts of geological formations on quality of groundwater in Navizak, Taleghan was studied. To examine sedimentary environment, we sampled formations and examined the samples at both microscopic and macroscopic scales. For hydrogeochemical analysis of water we used Piper, Stiff, Shuler, Wilcox, star, and composite diagrams. Saturation indices were analyzed using PHREEQC codes. The results indicate that hydrogeochemistry of groundwater at confined aquifers and aquitards is affected by geological formations of the region. At the north and northeast areas, aquitards are predominantly calcium bicarbonate layers. This layer is fed by Karaj formation and the quality observed in this zone is because the layer is located above the upper red formation (URF). The central and southern zones have waters of calcium-sulfate type with acceptable quality for drinking. This is the result of significantly thick layers of clay and marl which reduce hydraulic conductivity, improve water retention, and therefore, increase the amount of salts in groundwater. Although alluvial confined aquifers with layers of salt and gypsum lower the quality of groundwater, however, their undesirable effects can be neglected due to the narrow range of their presence.